2005
DOI: 10.1016/j.ssc.2005.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetoresistance at room-temperature in small-molecular-weight organic semiconductor sandwich devices

Abstract: We present an extensive study of a large, room temperature magnetoresistance (MR) effect in tris-(8-hydroxyquinoline) aluminum sandwich devices. The effect is similar to that previously discovered in p-conjugated polymer devices. We characterize this effect and discuss its dependence on magnetic field direction, voltage, temperature, film thickness, and electrode materials. The MR effect reaches almost 10% at fields of 10 mT at room temperature. The effect shows only a weak temperature dependence and is indepe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 22 publications
3
88
0
Order By: Relevance
“…3 Recently, organic magnetoresistance ͑OMR͒ of up to ϳ15% has been observed in a number of organic materials commonly used for organic light-emitting diodes ͑OLEDs͒, and here the mechanism is still unclear. [4][5][6][7][8] These observations have been made in device structures with no magnetic components, and the effect is found to correlate with the onset of light emission from the device, which suggests that the effect is excitonic in nature. 9 The term organic magnetoresistance is something of a misnomer as the effect is seen in devices that exhibit highly nonlinear current-voltage characteristics and hence cannot be considered as a resistance in the classical sense.…”
Section: Introductionmentioning
confidence: 76%
“…3 Recently, organic magnetoresistance ͑OMR͒ of up to ϳ15% has been observed in a number of organic materials commonly used for organic light-emitting diodes ͑OLEDs͒, and here the mechanism is still unclear. [4][5][6][7][8] These observations have been made in device structures with no magnetic components, and the effect is found to correlate with the onset of light emission from the device, which suggests that the effect is excitonic in nature. 9 The term organic magnetoresistance is something of a misnomer as the effect is seen in devices that exhibit highly nonlinear current-voltage characteristics and hence cannot be considered as a resistance in the classical sense.…”
Section: Introductionmentioning
confidence: 76%
“…A detailed study of the OMAR effect in Alq 3 devices can be found in the original publication [10]. Here only the room temperature data are shown in Fig.…”
Section: B Organic Magnetoresistance In Small Molecule Devicesmentioning
confidence: 99%
“…Recently there has been a growing interest in spin [4,5,6] and magnetic field effects [7,8,9,10,11,12,13,14] in these materials. During the study of sandwich devices made from the π-conjugated polymer polyfluorene (PFO) we recently discovered a large and intriguing magnetoresistive (MR) effect, which we dubbed organic magnetoresitance (OMAR).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the magnetic field on the current through the device was attributed to an increase in the electron injection due to singlet excitons reaching the cathode and dissociating. The effect of a magnetic field on the current through organic materials was investigated further by Mermer et al [4][5][6] They observed that organic magnetoresistance ͑OMR͒ can be observed in a number of different systems and that the effect could be both positive and negative. Desai et al 7 investigated the role of the cathode material on the OMR of a typical Alq 3 based OLED structure and found that the OMR was intimately correlated with the light emission from the device so that at drive voltages below "turn on," no OMR was observed.…”
Section: Introductionmentioning
confidence: 99%